DISKONTINUITAS KERJASAMA N UKLIR VENEZUELA DENGAN RUSIA PASCA HUGO CHAVEZ - Eka Fitriana (HI 15 UMY 421, 2015)
*421 This research focuses on the factors that affect on the discontinuities Venezuelan nuclear reactors cooperation with Russia during the reign of Nicolas Maduro. Whereas the construction of a nuclear reactor is intended to diversify the energy to Venezuela as national development efforts during the reign of Hugo Chavez. With a qualitative approach, this research emphasizes the content analysis method. Framework in this research departs from the political system theory and the theory of charismatic leadership by combining a political approach and actor. The results of this research indicate that the construction of nuclear reactors cooperation between Venezuela with Russia are affected by economic conditions, community support and leadership style between Hugo Chavez and Nicolas Maduro. Where the economic conditions faced by the election of President Nicolas Maduro.Since Nicolas Maduro elected on 2013, Venezuela economic conditions has decreased the inflation resulting from the decline in world oil prices, and rising crime in Venezuela. Moreover, that public support Venezuela on freezing and closing the construction of nuclear reactors also has affects the contuction itself, where people assume that Venezuela does not need a new energy such as nuclear. And also, that the government should prioritize the improvement of the domestic economy. In addition, the leadership style played by Nicolas Maduro in decisions regarding the development of nuclear reactors is different from the previous leader of Hugo Chavez. Where Hugo Chavez was able to change personal ambition to public interest.Which makes nuclear as political fantasy to gain the support of the Venezuelan people in the elections in 2012. And as well as political or economic bargaining with allies or enemies, and non-intervention, that of nuclear capabilites could deter or prevent intervention from other countries. But with Nicolas Maduro character who does not have a charisma like Hugo Chavez, he considers nuclear only as needed. Venezuela where a country rich in oil and natural gas do not need such as nuclear energy. Keywords: Nuclear, Charismatic Leadership, Political System, Venezuela